Psychological Needs in Spanish Pregnant Women During the Transition to Motherhood: A Qualitative Study - Patricia Catalá; Cecilia Peñacoba; Carmen Écija; Lorena Gutiérrez; Livia Gomes Viana Meireles (Societies)
Background: Motherhood involves significant identity transformation, encompassing physical, emotional, and social changes that can create tensions between a woman’s previous identity and her new maternal identity. In Spain, cultural expectations of motherhood can intensify this conflict, affecting the transition to the role of mother. This study explores the experiences and needs of Spanish women during the perinatal period, identifying common concerns and cultural particularities. Methods: A qualitative design using focus groups was employed. Thirty-three women from the Community of Madrid participated, with an average age of 28.42 years. Four focus groups were conducted: one with women in the third trimester of pregnancy, one with women in the early postpartum period (0–5 months), one with women in the late postpartum period (6–12 months), and one mixed group. Semi-structured questions guided the discussions, and thematic analysis was used to analyze the data. Findings: Nine main themes were identified: birth process, emotional management, acceptance of physical and mental changes, breastfeeding, sleep management, attachment and bonding, maternal identity, specialized resources, and setting limits. Key findings include the importance of mental and physical preparation for birth, managing emotions, and accepting bodily changes. Participants highlighted the need for emotional support, accurate information, and community resources. Conclusions: This study emphasizes the need for culturally sensitive perinatal support programs that provide tools for prenatal education, pain management, emotional support, and identity transition, integrating women’s prior identity to facilitate a harmonious transition to motherhood.